2003
DOI: 10.1111/j.1939-1676.2003.tb02523.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Dietary β‐Carotene on Immunological Variables in Dogs

Abstract: ␤-Carotene is a naturally occurring carotenoid reported to have health-promoting effects in several species. Advancing age is known to have a negative impact on various immune variables in several species. This study was conducted in order to assess the effect of age on immune response in dogs and to determine whether ␤-carotene is able to reverse this age-associated decline. To test this hypothesis, young and old dogs (n ϭ 36) were fed either a control diet or experimental diets containing supplemental ␤-caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…67 The results corroborated other work showing that both T-cell and B-cell populations in older dogs were reduced when compared with the populations of these cells in young adult dogs. 67 The results corroborated other work showing that both T-cell and B-cell populations in older dogs were reduced when compared with the populations of these cells in young adult dogs.…”
Section: Antioxidant Nutrientssupporting
confidence: 89%
“…67 The results corroborated other work showing that both T-cell and B-cell populations in older dogs were reduced when compared with the populations of these cells in young adult dogs. 67 The results corroborated other work showing that both T-cell and B-cell populations in older dogs were reduced when compared with the populations of these cells in young adult dogs.…”
Section: Antioxidant Nutrientssupporting
confidence: 89%
“…In humans, decreased T cell proliferation in the elderly is well documented, and has been associated with all-cause mortality(Effros and Walford, 1983; Ferguson et al, 1995; Jiang et al, 2007; Wayne et al, 1990). Several canine studies have also previously detected decreased lymphocyte proliferation in aged dogs although specific lymphocyte subsets were not assessed (Greeley et al, 2001; HogenEsch et al, 2004; Kearns et al, 1999; Massimino et al, 2003; Strasser et al, 2000). Notably, it has been suggested that these age-associated differences in lymphocyte function are a consequence of changes to the proportions of naïve and memory subsets that occur with age in humans; an explanation that would also explain our results in dogs(Ginaldi et al, 2001; Hoffmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Canine studies have determined that aged dogs display certain clinical characteristics of immunosenescence such as decreased antibody responses to novel pathogens and increased risk of cancers(Day, 2010; Fleming et al, 2011; Kearns et al, 1999; Kennedy et al, 2007). Corresponding evidence of decreasing immune function includes decreased proliferation of peripheral blood mononuclear cells (PBMCs), increased IFNγ expression by CD4+ T cells, and decreased proportions of CD45RA+ lymphocytes(Greeley et al, 2001; HogenEsch et al, 2004; Horiuchi et al, 2007; Massimino et al, 2003; Reis et al, 2005). Furthermore, a recent study showed that aged Labradors displayed a significant decrease in the number of clonal peaks in the locus encoding the T cell receptor (TCR) β chain variable region (TCRB V gene families) compared to young Labradors(Holder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This finding may reflect age-related immunologic changes similar to those proposed for humans. The canine immune system undergoes a process of age-related compromise in function, with declines in leukocyte proliferation, mitogen stimulation, chemotaxis, phagocytosis, and various other immunologic parameters 3638. These age-associated changes in immunity are similar between dogs and humans 39,40.…”
Section: Discussionmentioning
confidence: 99%